Amino acid supplementation supports growth and reproductive development under dietary restriction - Ndunguru, Sawadi F.; Reda, Gebrehaweria K.; Csernus, Brigitta; Gulyás, Gabriella; Knop, Renáta; Szabó, Csaba; Lendvai, Ádám Z.; Czeglédi, Levente (Frontiers in Animal Science, 2025)
IntroductionNutritional status influences developmental processes, including sexual maturation. While the effects of macronutrients on reproductive development are well studied, the role of specific amino acid composition in ovarian and follicular development in birds remains less explored. Here, we investigated the impact of dietary restriction and amino acid supplementation on growth and reproductive development of Japanese quail (Coturnix japonica).MethodsBirds were assigned to five dietary treatments: control (ad libitum), 20% dietary restriction (DR20), and DR20 supplemented with methionine (DR20+Met), leucine (DR20+Leu) or both (DR20+Leu+Met) at levels 20% above the recommended nutrient content.Results and discussionDietary restriction reduced body mass, ovary mass, ovary index, and total antioxidant capacity without affecting hierarchical follicle counts or size. However, supplementation with either amino acid improved these parameters from dietary restriction to the control levels. Furthermore, methionine supplementation alone or combination of methionine and leucine significantly increased follicle numbers, whereas leucine alone had no effect on hierarchical follicle numbers. Our findings underscore the importance of amino acids in mitigating the adverse effects of dietary restriction on growth, reproduction, and oxidative balance in birds at the onset of reproductive maturation.